Patient motivation and adherence to an on-demand app-based heart rate and rhythm monitoring infrastructure for atrial fibrillation management through teleconsultation. TeleCheck-AF project results. (19th May 2022) - Gawalko, M; Hermans, ANL; Van Der Velden, RMJ; Betz, K; Verhaert, DVM; Pluymaekers, NAHA; Vernooy, K; Sultan, A; Pison, L; Manninger, M; Duncker, D; Evans, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: TeleCheck-AF is a mobile health (mHealth) infrastructure developed to provide remote management and comprehensive care to patients with atrial fibrillation (AF) during the Covid disease-19 pandemic lockdown within cardiology centers in Europe. TeleCheck-AF integrates an on-demand photoplethysmography-based heart rate/rhythm monitoring application supported a scheduled teleconsultation. Purpose: The current sub-study of the TeleCheck-AF project aimed to provide the first real-world dataset on patient adherence and motivation to a standardized mHealth application integrated in remote AF management. Methods: Patients were instructed to perform 60-second app-based heart rate/rhythm recordings three times daily and in case of symptoms for seven consecutive days prior to teleconsultation. Motivation was defined as number of days in which the expected number of measurements (≥three/day) were performed per number of days over the entire prescription period. Adherence was defined as number of performed measurements per number of expected measurements over the entire prescription period. Results: Data from 990 consecutive patients with diagnosed AF (median age 64 [57-71] years, 39% female) from 10 centers that included the highest number of patients (≥25) were analyzed. Patients with both optimal motivation (100%) and adherence (≥100%) constituted 28% of the study population and had a lower percentage of recordings in sinus rhythm (90 [53-100%] vs 100 [64-100%], P<0.001) compared to others. Age and diabetes were predictors of both optimal motivation and adherence (odds ratio [OR] 1.02, 95% coincidence interval [95% CI] 1.01-1.04, P<0.001 and OR, 0.49, 95% CI 0.28-0.86, P=0.013, respectively). Patients with 100% motivation also had ≥100% adherence. Independent predictors for optimal adherence alone were age (OR 1.02, 95% CI 1.00-1.04, P=0.014), female sex (OR 1.70, 95% CI 1.29-2.23, P<0.001), previous AF ablation (OR 1.35, 95%CI 1.03-1.07, P=0.028). Conclusion: In the TeleCheck-AF project, older age and diabetes were predictors of optimal patient motivation and adherence to app-based heart rate/rhythm monitoring. Therefore, physicians, nurses and allied health specialists involved in the management and care for patients with AF should not be discouraged to provide a mHealth infrastructure to elderly patients. Patient engagement improves mHealth adherence/motivation, hence, it is crucial to tailor the mHelath intervention to the needs and preferences of the patient.